HUBUNGAN POLA ASUH ORANG TUA TERHADAP EMPATI PESERTA DIDIK SEKOLAH DASAR - Fajri, Riza Nurul; Hidayat, Rahmat; Ihsanda, Nu'man (Jurnal Intisabi, 2025)
Social sensitivity is formed from empathy that develops through supportive parenting. This study aims to determine the relationship between parenting patterns and empathy of elementary school students. The study involved 118 participants in grades IV, V, and VI at MIS Ciwahangan using a quantitative correlational approach. Likert scale questionnaire that had been verified by experts became the data collection tool. The results showed that almost all parents have an empathy level (81.84%) and apply parenting patterns according to indicators (78.25%). With a correlation coefficient of r = 0.509 and a significance value of 0.000, the correlation test results show a fairly strong relationship between parenting patterns and student empathy. This indicates that students' empathy levels increase as parenting practices improve, with the strength of the relationship being in the moderate range. Empathy that grows through supportive parenting plays an important role in shaping moral character and strengthening healthy social relationships.